Microstructure and properties degradation of P/T 91, 92 steels weldments in creep conditions - Falat L.; Homolová V.; Kepič J.; Svoboda M.; Výrostková A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The studies were performed on dissimilar ferritic/austenitic weldments between 9Cr tempered martensitic steels of the grades either P/T 91 or 92 and unstabilised AISI316H austenitic steel. The welded joints were fabricated using the fusion welding by tungsten inert gas (TIG) method with Ni-based filler metal. Microstructural analyses were performed using light and electron microscopy. Microstructural gradient in heat-affected zone (HAZ) of 9Cr steels remained preserved during creep exposure. All weldments fractured by the type IV failure within their intercritical HAZ (ICHAZ) regions. The most remarkable microstructural change during creep was the precipitation of intermetallic Laves phase. Experimentally determined phases of the samples after creep exposure are in good agreement with equilibrium thermodynamic calculations.